Android Based Coffee Dryer Temperature Control System Design - Fadillah, Rifky; Sukardi, Sukardi (Dinasti Information and Technology, 2023)
Development And application technology post-harvest need Keep going driven in effort push lost results And increase quality product so that capable increase income farmer specifically farmer small . Development sufficient coffee production rapidly the need supported with readiness technology And means suitable post- harvest For condition farmers to order them capable produce coffee beans with quality as required _ by National Standards Indonesia.Tasks end This aim For increase productivity coffee farmers when face bad weather _ friendly.with using DHT-22 sensors and sent using Bluetooth HC-05 to Android smartphone. To use For turn on heater so that coffee drying can walk Keep going continuously when face bad weather _ Good as well as capable increase productivity And quality small coffee farmer.Testing done for 3 days To use ensure tool Work with OK.testing This get results where Bluetooth is capable Work within a 5 meter radius without obstacle and the heater is capable light up more less than 1 hour when No There is sun depends from capacity battery.